2000
DOI: 10.1111/1467-6486.00214
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Collaboration Between Organizations: An Empirical Study Of Supply Chain Partnering

Abstract: Many managers attempt to develop collaborative alliances with other organizations. Such strategies are difficult to implement: they are as likely to fail as to succeeed. Implementing and managing an alliance is harder than deciding to collaborate. This paper explores the topic empirically through a study of one form of alliance -supply chain partnering. It presents an interaction model of partnering which shows seven contextual factors that shape, and are shaped by, human action. This context can both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(180 citation statements)
references
References 0 publications
5
170
0
5
Order By: Relevance
“…These findings support partly the conclusions from Boddy et al (2000) and Mason and Leek (2008). However, the notions of Mentzer et al (2001) or Lambert (2004) can be confirmed with respect to the importance of setting up the internal organizational conditions first, before entering into a supply chain partnership.…”
Section: Discussionsupporting
confidence: 74%
“…These findings support partly the conclusions from Boddy et al (2000) and Mason and Leek (2008). However, the notions of Mentzer et al (2001) or Lambert (2004) can be confirmed with respect to the importance of setting up the internal organizational conditions first, before entering into a supply chain partnership.…”
Section: Discussionsupporting
confidence: 74%
“…Ultimately, SCM-related processes impact on (4) the execution of SCM. This 'association hierarchy' pathway clearly confirms and adds to Boddy, Macbeth, and Wagner's (2000) notions on the drivers of supply chain partnering. This hierarchy is also in line with Grant's (1991) resource-based view on vertical inter-organisational networks, in suggesting that resources support the development of capabilities that then result in the development and maintenance of competitive advantage.…”
Section: Theoretical Implicationssupporting
confidence: 68%
“…A 'systematic approach' to development (Christopher & Juttner, 2000); recognition of the need to actively manage multiple actors' interests (Boddy et al, 1998) and equitable benefit sharing (Cox, 2001) have all been proposed as means of improving the likelihood of a successful outcome. Alternative interaction models (Boddy, Macbeth, & Wagner, 2000) and research by the IMP group (Ford, 1990;Gadde & Hakansson, 2001;Hakansson, Henjesand, & Waluszewski, 2004;Hakansson & Snehota, 1995) provide multi-faceted approaches with which to posit potential and explore actual interaction effects. Our research study contributes to and extends these endeavours.…”
Section: The Organizational Buyer-behaviour and Collaborative Partnermentioning
confidence: 99%